Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1074/jbc.m304632200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent Protein Interactions in MUC5B Provide Reversible Cross-links in Salivary Mucus

Abstract: The macromolecular organization within saliva was investigated by tracer diffusion measurements of fluorescent polystyrene microspheres by fluorescence recovery after photobleaching using a confocal microscope (confocal-FRAP). There was a concentrationdependent reduction in microsphere diffusion; this was much greater in the presence of calcium (10 mM) and was reduced by the addition of EGTA (10 mM). These effects on tracer diffusion showed that native saliva contained a macromolecular organization that was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
117
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 40 publications
7
117
0
Order By: Relevance
“…This is consistent with previous reports (Carlstedt et al, 1983;Perez and Proust, 1987;Durrrer et al, 1995;Lee et al, 2005;Raynal et al, 2003). In both wet and dry states, the extracted mucin was light-brownish in colour, with a pleasant meaty odour.…”
Section: Physicochemical Properties Of Snail Mucinsupporting
confidence: 82%
See 1 more Smart Citation
“…This is consistent with previous reports (Carlstedt et al, 1983;Perez and Proust, 1987;Durrrer et al, 1995;Lee et al, 2005;Raynal et al, 2003). In both wet and dry states, the extracted mucin was light-brownish in colour, with a pleasant meaty odour.…”
Section: Physicochemical Properties Of Snail Mucinsupporting
confidence: 82%
“…These features are ideal with respect to the formation of hydrogels. Studies have shown that reconstucted mucous gels from mucins have similar rheological properties as native mucous gels at physiological concentrations (Raynal et al, 2003). The ability of mucin to form the structural backbone of the mucous gel is one of its most important functions (Raynal et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic interactions alone cannot fully explain recovery of the hBD signal, since asialylation of saliva or use of other divalent cations other than calcium does not completely unmask the hBD signal in our ELISA-near-complete recovery of signal was obtained only with calcium. This unique calcium-dependent phenomenon could be due to calcium-induced changes in the intrinsic viscosity of saliva (35 ) and macromolecular contraction/folding of mucins (36 ), or calcium could be shielding the interactions between hBDs, sialic acid residues, and other negatively charged moieties.…”
Section: Discussionmentioning
confidence: 99%
“…Tracking motion of beads of varying sizes provides information about the mesh properties of mucus (28,29). In 2.5% mucus, 200-nm beads diffused over much greater distances than in 1-and 3-m beads, even when corrected for bead radius (Fig.…”
Section: Biophysical Properties Of Mucus Gelsmentioning
confidence: 99%